2006
DOI: 10.1177/014860710603000132
|View full text |Cite
|
Sign up to set email alerts
|

Feeding an Elemental Diet vs a Milk‐Based Formula Does Not Decrease Intestinal Mucosal Growth in Infant Pigs

Abstract: We conclude that intestinal mucosal growth and villus morphology are similar in pigs fed ED and FORM, despite higher cell proliferation and protein synthesis rates and lower lactase activity with ED. This implies that elemental diets may be as trophic as polymeric formulas to simultaneously provide nutrition and a stimulus for intestinal growth during bowel rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
4
7
0
Order By: Relevance
“…As noted for urea production, it appears that the intestinal absorptive flux of dietary AAs was a strong determinant of the flux of dietary nitrogen utilization for the synthesis of splanchnic proteins. This is consistent with the preferential utilization of rapidly absorbed dietary AAs in splanchnic tissues as compared with slowly absorbed AAs (20) and a higher stimulation of mucosal protein synthesis after ingestion of an elemental diet than after ingestion of intact milk protein (37). Unfortunately, to our knowledge, there are no data comparing the effect of hydrolyzed or intact protein on muscle protein synthesis and balance.…”
Section: Discussionsupporting
confidence: 72%
“…As noted for urea production, it appears that the intestinal absorptive flux of dietary AAs was a strong determinant of the flux of dietary nitrogen utilization for the synthesis of splanchnic proteins. This is consistent with the preferential utilization of rapidly absorbed dietary AAs in splanchnic tissues as compared with slowly absorbed AAs (20) and a higher stimulation of mucosal protein synthesis after ingestion of an elemental diet than after ingestion of intact milk protein (37). Unfortunately, to our knowledge, there are no data comparing the effect of hydrolyzed or intact protein on muscle protein synthesis and balance.…”
Section: Discussionsupporting
confidence: 72%
“…The elemental diet provided less calories and protein than the polymeric diet (165 kcal $ kg 21 body weight or intestinal cell morphology (crypt depth, villus height, and muscle thickness) at the end of the 6-d trial. In contrast to the aforementioned piglet study (86), Stoll et al (88) found that cell proliferation and protein synthesis, measured by the percentage of labeled crypt cells in the S-phase and ornithine decarboxylase activity, were considerably higher in the proximal jejunum and ileum of the piglets fed an elemental diet. Furthermore, concentrations of gut hormones GLP-2 and glucose-dependent insulinotropic polypeptide, but not peptide YY, were considerably higher in the elemental diet group.…”
Section: Sources Of Nutritionmentioning
confidence: 67%
“…Consistent with the "functional workload" hypothesis are observations in animals that polymeric formulas are more effective than semielemental ones in terms of body mass, growth, villus height, crypt depth, brush border enzymes, and barrier function (Bines et al 2002;Stoll et al 2006). In adult studies carried out in critically ill patients, the results are equivocal, and the recommendation is to use polymeric formulas (Heyland et al 2004).…”
Section: Nutrients: In What Form?mentioning
confidence: 83%